The Hypothetical Learning Trajectory on Addition in Mathematics GASING - Rully Charitas Indra Prahmana (SEAMEO Regional Centre for QITEP in Mathematics, 2015)
The purpose of this study is to look at the role of using Mathematics GASING (Math GASING) to help students understand and master the addition concept from the informal level (concrete) to the formal level. The research method used is design research with a preliminary design, teaching experiments, and retrospective analysis stages. This study describes how the Math GASING made a real contribution for students understanding of the concept of addition. The whole strategy and model that requires students to discover, to describe, and to discuss during the construction phase demonstrates how students can use their initial understanding of the addition concept. The stages in the learning trajectory have an important role in understanding the addition concept from informal level to formal level and also make the study of mathematics more easy, fun, and enjoyable.